Analysis of Gear Heat Treatment Deformation of 20CrMoH and 8620H Materials - Kai Wu; Jinyuan Tang; Siyuan Sun; Wen Shao (Jixie chuandong, 2019)
Based on the material structure thermodynamics and heat treatment commercial simulation software， combined with the heat treatment process of the driven gear of the actual vehicle final reducer， the heat treatment deformation of gears of 20CrMoH and 8620H materials are researched. Taking the driven gear of the final reducer as the research object， the performance database of 20CrMoH and 8620H materials is established by JMATPRO software， and the numerical analysis model of the gear carburizing and pre-cooling quenching process is established. By using DEFORM software simulation，the of heat treatment deformation information of 20CrMoH and 8620H gears is obtained. The research shows that， the carbon content and hardness of the 8620H gear surface are less than 20CrMoH material，compared with 20CrMoH， the 8620H gear heat treatment deformation is smaller and more uniform.